CLINICAL TRIALS OF DRUGS IN PEDIATRICS: PROBLEMS AND ACHIEVEMENTS - S.S. Zavidova; L.S. Namazova-Baranova; S.V. Topolyanskaya (Union of pediatricians of Russia, 2010)
The new drugs introduction in practice demands long multistage preliminary studying of efficacy and safety for children. The information on necessity of carrying out of such researches, on impossibility of «carrying over» of the data received in adult patients to children is given in this article. The historical inquiry confirming necessity of participation of the state for the decision of this problem and carrying out of clinical researches is presented. Key words: drugs, efficacy, safety, clinical trials, children. (Pediatric Pharmacology. - 2010; 7(1):6-14)